A distinct subpopulation of CD25(−) T-follicular regulatory cells localizes in the germinal centers - Wing, James Badger (Proc Natl Acad Sci U S A, 2017)
T-follicular helper (Tfh) cells differentiate through a multistep process, culminating in germinal center (GC) localized GC-Tfh cells that provide support to GC-B cells. T-follicular regulatory (Tfr) cells have critical roles in the control of Tfh cells and GC formation. Although Tfh-cell differentiation is inhibited by IL-2, regulatory T (Treg) cell differentiation and survival depend on it. Here, we describe a CD25(−) subpopulation within both murine and human PD1(+)CXCR5(+)Foxp3(+) Tfr cells. It is preferentially located in the GC and can be clearly differentiated from CD25(+) non–GC-Tfr, Tfh, and effector Treg (eTreg) cells by the expression of a wide range of molecules. In comparison to CD25(+) Tfr and eTreg cells, CD25(−) Tfr cells partially down-regulate IL-2–dependent canonical Treg features, but retain suppressive function, while simultaneously up-regulating genes associated with Tfh and GC-Tfh cells. We suggest that, similar to Tfh cells, Tfr cells follow a differentiation pathway generating a mature GC-localized subpopulation, CD25(−) Tfr cells.